¿Religión a pesar de la Ilustración? - Placencia, Luis; Enskat, Rainer (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The question of whether enlightenment is possible through science or necessary in spite of science, like the question of whether religion is necessary and possible in spite of enlightenment and science, has been on the agenda since the 18th century. With the great exception of Plato, the problem was only really understood by the philosophers of the 17th and 18th centuries. This paper deals with some of the issues that present Kant as the pinnacle of 18th century attempts to answer the above-mentioned philosophical questions.
Keywords: Religion; enlightenment; science; Plato; Kant